Structural design of the storage tank component for DOST-NCR's rainwater harvesting system using ferrocement technology - Tolentino, Jose Ireneo A.; Lumbera, Maxell P.; Tibon, Noriza R. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
This study aims to implement ferrocement technology for the construction of the storage tank component of the rainwater harvesting system to be constructed in the Department of Science & Technology - National Capital Region (DOST - NCR) Office at Bicutan, Taguig. Ferrocement has a very high tensile strength-to-weight ratio. This means that thin ferrocement structures can be made relatively light and watertight. Hence, ferrocement is an attractive material for the construction of tanks. For this project, the design guidelines of Philippine Center for Water and Sanitation (International Training Network Foundation) were adopted. To validate the design, the flexural strength of ferrocement design is checked against estimated design loads using a modified Test Method for Flexural Strength (Using Simple Beam with Center-Point Loading). In terms of flexural strength, it can be concluded from the results that the ferfocement tank was overdesigned since it went over the required modulus of mpture. Even though the design was proven to be sufficient, further study could be done to optimize the design with respect to its design loading.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Concrete tanks; Storm water retention basins -- Design and construction